Enhancing students’ creativity at research universities in Malaysia - Afshari, Mojgan; Siraj, Saedah; Ghani, M.F.A.; Razak, Ahmad Zabidi Abdul (Societe de Physique et d'Histoire Naturelle de Geneve, 2012)
Creativity is an important element in the development of educational organizations. Although many variables influence student’s creativity in universities, there is a reason to suspect that particularly the leadership behaviors’ of lecturers have powerful influences. In this study, we examined leadership behaviors contributing to enhancement of the student’s creativity. Findings of this study indicated that the leadership behaviors of lectures (e.g., idealized influence, intellectual stimulation, inspirational motivation, technical skills, and involvement) can influence student’s creativity, both directly and indirectly. The leadership behaviors of lectures may nurture or stifle the student’s creative potential. The implications of these findings for theory and practice are discussed.